Gambaran Perilaku tentang Probiotik pada Mahasiswa Kesehatan Universitas Andalas: Behavioral Overview of Probiotics among Health Students at Andalas University - Hamelda Fajri Weirpa; Sovia Susianty; Susmiati (NERS Jurnal Keperawatan, 2024)
Probiotics are bacteria that have a medicinal effect when taken in appropriate quantities. The general populace is unaware about probiotics and their consumption. The purpose of this study is to examine the behavioral description of probiotics, which includes knowledge, attitudes, and actions surrounding probiotics in health students at Andalas University. The research approach is descriptive, with a non-probability sampling technique based on quota sampling. This study's sample size was 364 Andalas University health students. Data from a questionnaire on probiotic knowledge, attitudes, and activities. According to the findings of this survey, the majority of respondents (94.8%) had good and sufficient knowledge, nearly half (43.7%) had sufficient and less (41.8%) attitudes, and almost half (44.5%) had sufficient and insufficient (40.4%) activity. It is hoped that Andalas University will provide extra learning on probiotics in order to increase probiotic behavior in Andalas University health students.